Socio‑Technical Pathways To Resilience: Indigenous Women Entrepreneurs In Papua Mountains - Nanang Gunawan; Ayu Anggraini Tambunan; Defran Defran Siska (UNIVED Press, 2026)
This study examines the entrepreneurial resiliency of indigenous Dani women entrepreneurs in Papua Pegunungan by analyzing the roles of digital literacy, dynamic capabilities, and adversity quotient through a mixed‑methods design. Quantitative data from 181 respondents were analyzed using Partial Least Squares Structural Equation Modeling (PLS‑SEM), while qualitative insights were obtained through a Delphi process. Results confirmed that digital literacy has both a strong direct effect on resiliency and an indirect effect mediated by dynamic capabilities, supporting all hypotheses. Qualitative findings revealed that digital literacy is practiced collectively, often through shared devices and platforms such as WhatsApp, serving as connective infrastructure rather than individual proficiency. Dynamic capabilities were expressed through communal improvisation, ecological awareness, and tacit knowledge, while resilience was sustained through solidarity and cooperation. Adversity quotient further enabled entrepreneurs to reframe limitations as shared challenges. The study advances a socio‑technical understanding of resiliency and offers guidance for inclusive entrepreneurship policies tailored to indigenous contexts.